Lead(II)-Azido Metal–Organic Coordination Polymers: Synthesis, Structure and Application in PbO Nanomaterials Preparation - Jaber Dadashi; Mohammad Khaleghian; Younes Hanifehpour; Babak Mirtamizdoust; Sang Woo Joo (Nanomaterials, 2022)
The current study aims to explain recent developments in the synthesis of Pb(II)-azido metal-organic coordination polymers. Coordination polymers are defined as hybrid materials encompassing metal-ion-based, organic linkers, vertices, and ligands, serving to link the vertices to 1D, 2D, or 3D periodic configurations. The coordination polymers have many applications and potential properties in many research fields, primarily dependent on particular host–guest interactions. Metal coordination polymers (CPs) and complexes have fascinating structural topologies. Therefore, they have found numerous applications in different areas over the past two decades. Azido-bridged complexes are inorganic coordination ligands with higher fascination that have been the subject of intense research because of their coordination adaptability and magnetic diversity. Several sonochemical methods have been developed to synthesize nanostructures. Researchers have recently been interested in using ultrasound in organic chemistry synthetics, since ultrasonic waves in liquids accelerate chemical reactions in heterogeneous and homogeneous systems. The sonochemical synthesis of lead–azide coordination compounds resulted from very fantastic morphologies, and some of these compounds are used as precursors for preparing nano lead oxide. The ultrasonic sonochemistry approach has been extensively applied in different research fields, such as medical imaging, biological cell disruption, thermoplastic welding, food processing, and waste treatment. CPs serve as appropriate precursors for preparing favorable materials at the nanoscale. Using these polymers as precursors is beneficial for preparing inorganic nanomaterials such as metal oxides.